March of the "Corps Editorial" : The Development of Journalism in North Carolina, 1796-1860 - Clark, McIver Allen, Jr. (East Carolina University, 2013)
North Carolina print culture enjoyed significant and steady expansion after the appointment of James Davis as state printer in 1749. Though often marginalized in a national context, North Carolina's newspapers developed in influence and number steadily from 1749 to 1860. First called to publish a uniform rendering of state law, North Carolina's leading newspapers became heavily politicized in the 1790's despite the pressures of the 1798 Sedition Act. The first attempt to create a nonpartisan, popular paper emerged in 1808. As politicized weeklies sought patronage from officeholders and their benefactors, nonpartisan success proved that subscribers and advertising patronage could fuel profits independently from politics.  This thesis follows a chronology of newspaper development and economy in the state as it evolved during the late colonial and antebellum period. It examines the financing required to both establish and maintain presses and surveys the returns on newspaper investments for owners, the benefits to professionals engaged in the day-to-day printing trade, and the significance to North Carolinians. This study argues that editors leveraged political power was steadily augmented and leveraged into commercial success by editors during the period from 1749-1861.
Keywords: American history; American newspapers--North Carolina--History--18th century; American newspapers--North Carolina--History--19th century; Alien and Sedition laws, 1798; Davis, James, 1721-1785; North Carolina--History--18th century; North Carolina--History--19th century